Penerapan Ice Breaking dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 1 Panti Kabupaten Pasaman - Rahmawita Rahmawita; Junaidi Junaidi; Albaihaqi Anas; Iswantir M (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Teachers rarely apply Ice Breaking, where the teacher only provides ice breaking by looking at the students' condition, if it is not conducive then the teacher plays a game or an activity in between lessons. During the ice breaking, some students were not focused, there were students who were sleepy and even fell asleep in class. This research uses a qualitative approach. With data collection techniques through observation and interviews. The key informant was the Islamic Religious Education teacher and the supporting informants were class VIII students and the school principal. Data analysis in this research involves data reduction, data display, and then conclusions. Based on the research results, it was found: The research results showed that the first application of ice breaking in learning Islamic religious education in class VIII of SMP Negeri 1 Panti Pasaman Regency was that the teacher only provided ice breaking depending on the condition of the students. The types of ice breaking used by teachers include stories, games, counting, singing (sholawat). The two obstacles faced by teachers when implementing ice breaking are students playing around, students who don't understand, are nosy with friends, like to talk to friends, students who are lazy to follow the movements, and indeed difficult to manage who like to do whatever they want and lack of concentration in students' learning because they only Focus only on the ice breaking moment. However, teachers can overcome these obstacles so that students generally focus more on learning.